The study on post-operative wound infections at Vizianagaram in Andhra Pradesh, India - Rao, B. Hemashankara; Chakravarthy, K. Srinivasa (International Journal of Research in Medical Sciences, 2016)
Background: In most of the people post-operative wound infections are responsible for major complications such as cost, morbidity, mortality and duration of hospital stay related to surgeries. Objectives of the study were to demonstrate the incidence of post-operative wound infections at MIMS (Maharagah’s Institute of Medical Sciences, Vizianagaram. Methods: A cross sectional study has been carried out to know the incidence of post-operative wound infection The study was conducted in MIMS (Maharagah’s Institute of Medical Sciences). The study population was enrolled after fulfilling the selection criteria from General Surgery 100 patients (both elective and emergency surgeries) were selected using randomized technique. Results: Out of 100 cases in the study 17 were positive for post-operative wound infection and out of which 10 were mild infections, 9 cases were moderate infections and 3 were severe infections including 1 burst abdomen. Coagulase positive Staph aureus was isolated in 10 out 40. Over all infection rate in the study was 13.58%. Conclusions: The study clearly depicted the changing pattern of wound infection toward mixed infection. A larger study with substantial number of patients will confirm the findings of this study.